Assessment of students’ attitudes and environmental behavior at School of Allied Health Sciences of Polytechnic Institute of Porto - Nunes, Mafalda (2014)
In recent decades, the sustainability in higher education institutions has become an important issue for these institutions, as they realised their impacts in the environment and became more aware of their responsibilities to the society. Sustainability also presents an opportunity to promote new approaches in education such as problem based learning, more interdisciplinary and applied learning (Corcoran et al., 2004). As one of the key elements in these institutions, students play an important role, and their attitudes and environmental behaviour have a strong impact in the sustainability of the institutions and, as stated by Zsóka et al. (2013),students who behave in a consistently pro-environmental manner are drivers of a more sustainable future. It is crucial to know the students attitudes and environmental behaviour in order to promote, for example, effective environmental education.